Efficient long-acting antirust agent and preparation method thereof

By combining silicon sol to modify the composite materials in epoxy emulsion and anti-rust filler, the problems of poor permeability and insufficient stability caused by high surface tension of existing aqueous epoxy emulsions are solved, and efficient and long-term anti-rust effect is achieved .

CN119391269APending Publication Date: 2025-02-07JIANGSU YISA BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411805079.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The surface tension of existing aqueous epoxy emulsions is high, resulting in poor permeability and spreadability, making it difficult to form effective protection in small locations such as narrow slits and pores, and the stability is poor, which limits the long-term effectiveness of rust prevention.

Method used

Using silicon sol combined modified epoxy emulsion, the surface tension of the epoxy emulsion is reduced, its permeability ductility is enhanced, and zinc molybdate is used in the anti-rust filler. With phyticated graphene oxide composite materials, it forms layers of anti-permeable structures to improve the density and stability of the anti-rust agent.

Benefits of technology

It significantly improves the permeability and spreadability of the anti-rust agent, enhances the protection effect on the metal surface, extends the anti-rust cycle, and ensures that good anti-rust performance can be maintained in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391269A_ABST
    Figure CN119391269A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient long-acting antirust agent and a preparation method thereof, and relates to the technical field of antirust agents. The high-efficiency long-acting antirust agent is prepared from a silica sol combined modified epoxy emulsion, an antirust filler, a TEGO-755W dispersing agent, a TEGO-812 defoaming agent, nano zinc oxide, an EH2168 epoxy curing agent and deionized water. The silica sol combined modified epoxy emulsion is composed of a water-based four-functionality epoxy emulsion and silica sol. The anti-rust filler is added into the silica sol combined modified epoxy emulsion, so that the compactness, spreadability and water resistance of the coating are improved, narrow slits, pores and other positions can be effectively protected, the invasion path of a corrosive medium is prolonged, and therefore, the anti-rust coating has efficient anti-rust performance, and meanwhile, the service life of the coating is prolonged. The heat resistance and the stability of the coating are further improved, and the long-term effective anti-rust effect can still be achieved even in severe environments such as high temperature and high humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rust inhibitors, and specifically relates to a high-efficiency and long-acting rust inhibitor and a preparation method thereof. Background Art

[0002] With the continuous development of industrial technology, metal materials are increasingly used in various fields. However, metal materials are easily affected by environmental factors and rust during processing, storage and use, which not only affects the performance and life of the materials, but also increases production costs and maintenance difficulties. Traditional metal material rust prevention methods mainly include the use of heavy metal solutions and the application of anti-rust oils. Although these methods have a certain degree of anti-rust effect, there are problems such as environmental pollution, inconvenient construction, and short anti-rust period. With the increasingly stringent environmental protection laws and regulations and the advancement of sustainable development strategies, the development of a new type of environmentally friendly, efficient, and long-term anti-rust material has become a research hotspot in the industry.

[0003] In recent years, water-based anti-rust materials have attracted widespread attention for their advantages such as environmental protection, safety, and easy construction. Among them, high-performance, environmentally friendly anti-rust thin-film type film-forming materials with water-based epoxy resin as the main film-forming material can dry quickly at room temperature and are easy to construct. They are of great significance for promoting the greening and efficiency of metal material anti-rust technology.

[0004] The existing technology currently has the following problems:

[0005] The surface tension of water-based epoxy emulsion is large, which makes its penetration and spreading ability poor, making it difficult to effectively protect narrow gaps, pores and other small locations, making them prone to corrosion. At the same time, the stability of water-based epoxy emulsion is poor, which limits the long-term effectiveness of rust prevention. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a high-efficiency and long-lasting rust inhibitor, comprising the following components in parts by weight: 50-60 parts of silica sol combined with modified epoxy emulsion, 8-12 parts of rust-proof filler, 3-5 parts of TEGO-755W dispersant, 3-5 parts of TEGO-812 defoamer, 5-8 parts of nano zinc oxide, 15-20 parts of EH2168 epoxy curing agent, and 10-20 parts of deionized water.

[0007] The silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 30-50 parts of water-based four-functional epoxy emulsion and 20-30 parts of silica sol.

[0008] The anti-rust filler comprises the following components in parts by weight: 0.5-10 parts of phytated graphene oxide, 40-50 parts of ammonium molybdate tetrahydrate, and 60-70 parts of zinc acetate dihydrate.

[0009] The preparation method of the silica sol combined with modified epoxy emulsion specifically comprises the following steps:

[0010] (1) Add polyetheramine M-3085, AGE and 1 / 2 amount of tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer, stir evenly, heat to 100-110°C, then add the remaining amount of tetrafunctional epoxy resin EMTE350, continue to react for 1-2 hours, cool to 85°C after the reaction, transfer the mixture to a high-speed disperser, add 100-150mL of deionized water, perform shear dispersion for 0.5-1 hour, control the speed at 1600-1800rpm, reduce to room temperature and discharge, use polyetheramine as a hydrophilic chain extender and AGE as a regulator to emulsify the tetrafunctional epoxy resin to form a stable epoxy emulsion. At the same time, the addition of the hydrophilic chain extender can reduce the surface tension of the epoxy emulsion, promote the penetration of the emulsion into smaller locations, enhance the effectiveness and comprehensiveness of the anti-rust effect, and obtain a water-based tetrafunctional epoxy emulsion;

[0011] (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 10-20 mL of water, stir evenly, then add citric acid, and dissolve it by ultrasonication. The ultrasonic temperature is 30-40°C, the ultrasonic power is 600-800W, and the ultrasonic time is 20-30 minutes. The silica sol has good film-forming properties and stability, and can form a dense protective film on the metal surface, effectively isolating oxygen and moisture in the air, and preventing the oxidation process of the metal surface. The protective film formed by the silica sol has excellent weather resistance and corrosion resistance, and can maintain the anti-rust effect for a long time in harsh environments. It can resist the influence of harsh environments such as high temperature and high humidity, and maintain stable and effective anti-rust ability. , To obtain silica sol;

[0012] (3) adding the silica sol described in step (2) to the water-based tetrafunctional epoxy emulsion described in step (1), stirring for 5-15 minutes, and then ultrasonicating for 5-15 minutes, using the silica sol as a film-forming matrix to perform composite modification on the water-based tetrafunctional epoxy emulsion, firstly reducing the surface tension of the epoxy emulsion, further promoting the penetration and extension of the epoxy emulsion, and secondly the uniform microscopic pore structure formed by the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, uniform and smooth, which helps to maintain a long-term stable and effective anti-rust effect, and then, the water resistance of the silica sol can improve the disadvantage of the epoxy emulsion being easy to absorb moisture, reduce the adverse effects of moisture on the curing efficiency of the epoxy emulsion and the adhesion effect after curing, and obtain the silica sol-modified epoxy emulsion;

[0013] Preferably, in step (1), the molar amount of polyetheramine M-3085, AGE and tetrafunctional epoxy resin EMTE350 is 0.1 mol, which is conducive to the grafting reaction between the reactants and the tetrafunctional epoxy resin, improves the dispersibility of the epoxy emulsion, and is also conducive to exerting the adhesion and corrosion resistance of the tetrafunctional epoxy resin to the metal surface, and better resisting the adverse effects of the external environment;

[0014] Preferably, in step (2), the amount of citric acid added is 0.4-0.6 g. Citric acid can adjust the pH value of the sol to keep it in a stable acidic and alkaline environment, which is beneficial to improving the coating properties.

[0015] The preparation method of the rust-proof filler specifically comprises the following steps:

[0016] a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear and take out, add 20.0g graphite powder and stir evenly, put it into a blast drying oven at 80℃ to react for 5-6h, pour the pre-oxidized product into 3-5 times the amount of deionized water, wash and filter it to neutrality for many times, dry it at 60℃ for 10-12h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, place it in an ice water bath and stir it mechanically to make it uniform, then add 60.0g potassium permanganate, slowly heat to 35℃ and react for 1-2h, then add 920mL deionized water at a uniform rate, and control the temperature at 8℃ during the reaction. 5℃, then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, then add 80mL concentrated hydrochloric acid, let stand, wash 3-5 times with 30-35% hydrochloric acid aqueous solution, put into dialysis bag for dialysis, remove impurity ions, ultrasonically disperse in anhydrous ethanol, filter, freeze-dry, the graphene oxide obtained by chemical oxidation contains a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, epoxy, etc., which not only improves its solubility in polar solvents, but also makes the graphene oxide easy to modify, which can further enhance its anti-corrosion performance. Moreover, the lamellar structure of graphene oxide can effectively inhibit the infiltration, penetration and diffusion of corrosive media to obtain graphene oxide;

[0017] b. Weigh 0.1-0.2 g of the graphene oxide described in step a and add it to 150 mL of deionized water, ultrasonicate for 2-3 h to make it evenly dispersed, then add 1-3 mL of a phytic acid aqueous solution with a mass fraction of 60-70%, continue ultrasonication for 20-30 min, then stir and reflux in an oil bath at 80-100 ° C for 8-12 h, filter and wash until neutral, and freeze-dry. The addition of phytic acid makes the sheet structure of graphene oxide more irregular, and the sheets are cross-linked and stacked with each other, which increases the specific surface area and the amount of wrinkles, thereby enhancing the shielding performance, which is conducive to achieving a better anti-rust effect. In addition, phytic acid can also form complexes with metal ions such as iron, reduce the activity of metal ions, inhibit their generation and oxidation, thereby extending the durability of the anti-rust coating, improving its anti-rust performance, and obtaining phytic acidized graphene oxide;

[0018] c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions, weigh 0.4-0.5 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water, and dissolve 0.6-0.7 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion, stir for 4-5 hours to ensure sufficient adsorption of zinc ions, then drop the ammonium molybdate solution into the mixed solution, add ammonia water to adjust the pH to 8.0, then filter, wash, and dry to prepare A composite material of zinc molybdate and phytated graphene oxide is obtained. Since both zinc molybdate and phytated graphene oxide have a flaky structure, the composite material formed by the two is similar to a sandwich structure, which prolongs the penetration path of the external corrosive medium. At the same time, the composite material has a large surface area, and there is a certain distance between zinc molybdate particles, which is conducive to the synergistic effect of the two. The introduction of phytated graphene oxide improves the dispersibility of zinc molybdate particles, and zinc molybdate also reduces the aggregation of phytated graphene oxide, significantly improving the protective effect of the anti-rust coating, and obtaining an anti-rust filler.

[0019] Preferably, in step c, the amount of phytated graphene oxide added is 50-100 mg. The structural characteristics of phytated graphene oxide increase the loading amount and loading stability of zinc ions.

[0020] The present invention also provides a method for preparing a high-efficiency and long-acting rust inhibitor, which specifically comprises the following steps:

[0021] Disperse the anti-rust filler in 10-20mL deionized water, add it to the silica sol-modified epoxy emulsion at a speed of 500-600rpm, then add TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide. The antibacterial and antifungal effect of nano zinc oxide also has a positive effect on the anti-rust performance of the coating. Stir for 4-5h, then add EH2168 epoxy curing agent, and continue stirring for 5-10min. The prepared anti-rust coating can be sprayed on the metal surface to form a protective layer to effectively resist oxidation and corrosion. The anti-rust filler constructs a layer of anti-penetration structure in the silica sol-modified epoxy emulsion, increases the density and spreadability of the coating, prolongs the invasion path of the corrosive medium, and expands the extension range of the coating. At the same time, it also reduces the entry of water molecules, improves the heat resistance and stability of the coating, and enables it to maintain a good anti-rust effect even in harsh environments. Therefore, it is endowed with long-lasting and efficient anti-rust performance to obtain an efficient and long-lasting rust inhibitor.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The present invention increases the density, spreadability and water resistance of the coating by adding anti-rust filler to the silica sol-modified epoxy emulsion, which can not only effectively protect narrow gaps, pores and other locations, but also prolong the invasion path of corrosive media, thereby having efficient anti-rust performance. At the same time, it further improves the heat resistance and stability of the coating, and can achieve long-term and effective anti-rust effect even in harsh environments such as high temperature and high humidity. In the silica sol-modified epoxy emulsion, silica sol is used as a film-forming matrix to modify the water-based tetrafunctional epoxy emulsion, thereby reducing the surface tension of the epoxy emulsion and facilitating the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure of the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, which is conducive to ensuring long-term stable and effective anti-rust ability. In addition, the addition of silica sol can also act as an anti-precipitation agent to reduce the precipitation of solid substances such as other fillers, so that each component can fully exert its maximum performance. In the anti-rust filler, A composite material of zinc molybdate and phytated graphene oxide is formed, which has a large surface area and a sandwich-like structure, significantly prolongs the penetration path of external corrosive media, and the presence of each other is also beneficial to the dispersibility of the other component, reduces the agglomeration of particles, and helps to better play the synergistic effect of the two on anti-rust performance. The anti-rust filler is used in the silica sol combined with the modified epoxy emulsion, which further enhances the water resistance and heat resistance of the system, is beneficial to reduce the surface tension of the system, and also enhances the stability of the system in a high temperature and high humidity environment, thereby helping to exert long-term and efficient anti-rust performance; the present invention uses silica sol combined with modified epoxy emulsion, anti-rust filler, TEGO-755W dispersant, TEGO-812 defoamer, nano zinc oxide, EH2168 epoxy curing agent and deionized water to prepare a high-efficiency and long-term rust inhibitor, which significantly prolongs the invasion path of corrosive media, can effectively penetrate into small locations, and can still play a stable role in a high temperature and high humidity environment, thereby having efficient and long-term anti-rust protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the silica sol-modified epoxy emulsion prepared in Example 1 of the present invention;

[0025] Figure 2 This is a scanning electron microscope image of the rust-proof filler prepared in Example 1 of the present invention;

[0026] Figure 3 The rust rate results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0027] Figure 4 The graph is a result of the corrosion rate of Examples 1-4 of the present invention and Comparative Examples 1-3 at different times under high temperature and high humidity. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0031] Example 1

[0032] This embodiment proposes a high-efficiency and long-lasting rust inhibitor, comprising the following components in parts by weight: 60 parts of silica sol combined with modified epoxy emulsion, 12 parts of rust-proof filler, 5 parts of TEGO-755W dispersant, 5 parts of TEGO-812 defoamer, 8 parts of nano zinc oxide, 20 parts of EH2168 epoxy curing agent, and 20 parts of deionized water.

[0033] The silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 50 parts of water-based four-functional epoxy emulsion and 30 parts of silica sol.

[0034] The rust-proof filler comprises the following components in parts by weight: 10 parts of phytated graphene oxide, 50 parts of ammonium molybdate tetrahydrate, and 70 parts of zinc acetate dihydrate.

[0035] The preparation method of silica sol combined with modified epoxy emulsion specifically comprises the following steps:

[0036] (1) Add polyetheramine M-3085, AGE and 1 / 2 of the tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer. The molar dosage of polyetheramine M-3085, AGE and the tetrafunctional epoxy resin EMTE350 is 0.1 mol, which is beneficial to the grafting reaction between the reactants and the tetrafunctional epoxy resin, improves the dispersibility of the epoxy emulsion, and is also beneficial to the adhesion and corrosion resistance of the tetrafunctional epoxy resin to the metal surface, and better resists the adverse effects of the external environment. Stir evenly, heat to 110°C, and then add the remaining amount of The tetrafunctional epoxy resin EMTE350 was added, and the reaction was continued for 2 hours. After the reaction was completed, the temperature was lowered to 85°C, and the mixture was transferred to a high-speed disperser. 150 mL of deionized water was added, and shear dispersion was performed for 1 hour. The speed was controlled at 1800 rpm, and the material was discharged at room temperature. The tetrafunctional epoxy resin was emulsified with polyetheramine as a hydrophilic chain extender and AGE as a regulator to form a stable epoxy emulsion. At the same time, the addition of the hydrophilic chain extender can reduce the surface tension of the epoxy emulsion, promote the emulsion to penetrate into smaller positions, and enhance the effectiveness and comprehensiveness of the anti-rust effect, thereby obtaining a water-based tetrafunctional epoxy emulsion.

[0037] (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 20 mL of water, stir evenly, then add citric acid, the amount of citric acid added is 0.6 g, citric acid can adjust the pH value of the sol, keep it in a stable acid-base environment, which is beneficial to improve the coating property, and dissolve it by ultrasound, the ultrasound temperature is 40°C, the ultrasound power is 800W, and the ultrasound time is 30 minutes. The silica sol has good film-forming property and stability, and can form a dense protective film on the metal surface, effectively isolating oxygen and moisture in the air, and preventing the oxidation process of the metal surface. The protective film formed by the silica sol has excellent weather resistance and corrosion resistance, can maintain the anti-rust effect for a long time in harsh environments, can withstand the influence of harsh environments such as high temperature and high humidity, and maintain stable and effective anti-rust ability, thereby obtaining silica sol;

[0038] (3) Add the silica sol described in step (2) to the water-based tetrafunctional epoxy emulsion described in step (1), stir for 15 minutes, and then ultrasonicate for 15 minutes. Use the silica sol as a film-forming matrix to perform composite modification on the water-based tetrafunctional epoxy emulsion. First, the surface tension of the epoxy emulsion is reduced, which further promotes the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure formed by the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, uniform and smooth, which helps to maintain a long-term stable and effective anti-rust effect. Then, the water resistance of the silica sol can improve the disadvantage of the epoxy emulsion that it is easy to absorb moisture, reduce the adverse effects of moisture on the curing efficiency of the epoxy emulsion and the adhesion effect after curing, and obtain the silica sol-modified epoxy emulsion.

[0039] The preparation method of the rust-proof filler specifically comprises the following steps:

[0040] a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear and take out, add 20.0g graphite powder and stir evenly, put it into a blast drying oven at 80℃ to react for 6h, pour the pre-oxidized product into 5 times the amount of deionized water, wash and filter it to neutrality several times, dry it at 60℃ for 12h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, place it in an ice water bath and stir it mechanically to make it uniform, then add 60.0g potassium permanganate, slowly heat to 35℃ and react for 2h, then add 920mL deionized water at a uniform rate, and control the temperature at 85℃ during this period , then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, then add 80mL concentrated hydrochloric acid, let stand, wash 5 times with 35% hydrochloric acid aqueous solution, put into dialysis bag for dialysis, remove impurity ions, ultrasonically disperse in anhydrous ethanol, filter, freeze-dry, the graphene oxide obtained by chemical oxidation contains a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups, which not only improves its solubility in polar solvents, but also makes the graphene oxide easy to modify, which can further enhance its anti-corrosion performance. Moreover, the lamellar structure of graphene oxide can effectively inhibit the infiltration, penetration and diffusion of corrosive media to obtain graphene oxide;

[0041] b. Weigh 0.2 g of the graphene oxide described in step a and add it to 150 mL of deionized water, ultrasonicate for 3 h to make it evenly dispersed, then add 3 mL of a phytic acid aqueous solution with a mass fraction of 70%, continue ultrasonication for 30 min, then stir and reflux in an oil bath at 100 ° C for 12 h, filter and wash until neutral, and freeze-dry. The addition of phytic acid makes the sheet structure of graphene oxide more irregular, and the sheets are cross-linked and stacked with each other, which increases the specific surface area and the amount of wrinkles, thereby enhancing the shielding performance, which is conducive to achieving a better anti-rust effect. In addition, phytic acid can also form complexes with metal ions such as iron, reduce the activity of metal ions, inhibit their generation and oxidation, thereby extending the durability of the anti-rust coating, improving its anti-rust performance, and obtaining phytic acidized graphene oxide;

[0042] c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions. The amount of phytated graphene oxide added is 100 mg. The structural characteristics of phytated graphene oxide increase the loading capacity and loading stability of zinc ions. Weigh 0.5 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water. Dissolve 0.7 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion and stir for 5 h to ensure sufficient adsorption of zinc ions. Then, drop the ammonium molybdate solution into the mixed solution, and add ammonia water to adjust. The pH value is lowered to 8.0, and then filtered, washed and dried to prepare a composite material of zinc molybdate and phytic acid graphene oxide. Since both zinc molybdate and phytic acid graphene oxide have flaky structures, the composite material formed by the two is similar to a sandwich structure, which prolongs the penetration path of the external corrosive medium. At the same time, the composite material has a large surface area, and there is a certain distance between the zinc molybdate particles, which is conducive to the synergistic effect of the two. The introduction of phytic acid graphene oxide improves the dispersibility of the zinc molybdate particles, and zinc molybdate also reduces the aggregation of phytic acid graphene oxide, which significantly improves the protective effect of the anti-rust coating to obtain an anti-rust filler.

[0043] This embodiment provides a method for preparing a high-efficiency and long-acting rust inhibitor, which specifically comprises the following steps:

[0044] The anti-rust filler was dispersed in 20 mL of deionized water, and then added to the silica sol-modified epoxy emulsion at a speed of 600 rpm, followed by the addition of TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide. The antibacterial and antifungal effect of nano zinc oxide also has a positive effect on the anti-rust performance of the coating. The mixture was stirred for 5 hours, and then EH2168 epoxy curing agent was added. The stirring was continued for 10 minutes. The prepared anti-rust coating can be sprayed on the metal surface to form a protective layer to effectively resist oxidation and corrosion. The anti-rust filler constructed a layer of anti-penetration structure in the silica sol-modified epoxy emulsion, which increased the density and spreadability of the coating, extended the invasion path of the corrosive medium, and expanded the extension range of the coating. At the same time, it also reduced the entry of water molecules, improved the heat resistance and stability of the coating, and enabled it to maintain a good anti-rust effect even in harsh environments. Thus, it is endowed with long-lasting and efficient anti-rust performance, and a high-efficiency and long-lasting rust inhibitor is obtained.

[0045] In this example, the prepared silica sol combined with modified epoxy emulsion and anti-rust filler was subjected to scanning electron microscopy to observe its microscopic morphology. Figure 1 This is a SEM image of the silica sol combined with the modified epoxy emulsion prepared in Example 1, magnified 1000 times. Figure 2 The SEM image of the rust-proof filler prepared in Example 1 was magnified 400 times. Figure 1The structure of the silica sol combined with the modified epoxy emulsion prepared in this embodiment is firm and water-resistant. Figure 2 The rust-proof filler prepared in this embodiment has a larger surface area.

[0046] Example 2

[0047] This embodiment proposes a high-efficiency and long-lasting rust inhibitor, comprising the following components in parts by weight: 50 parts of silica sol combined with modified epoxy emulsion, 8 parts of rust-proof filler, 3 parts of TEGO-755W dispersant, 3 parts of TEGO-812 defoamer, 5 parts of nano zinc oxide, 15 parts of EH2168 epoxy curing agent, and 10 parts of deionized water.

[0048] The silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 30 parts of water-based four-functional epoxy emulsion and 20 parts of silica sol.

[0049] The rust-proof filler comprises the following components in parts by weight: 0.5 parts of phytated graphene oxide, 40 parts of ammonium molybdate tetrahydrate, and 60 parts of zinc acetate dihydrate.

[0050] The preparation method of silica sol combined with modified epoxy emulsion specifically comprises the following steps:

[0051] (1) Add polyetheramine M-3085, AGE and 1 / 2 of the tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer. The molar amount of polyetheramine M-3085, AGE and the tetrafunctional epoxy resin EMTE350 is 0.1 mol, which is beneficial to the grafting reaction between the reactants and the tetrafunctional epoxy resin, improves the dispersibility of the epoxy emulsion, and is also beneficial to the adhesion and corrosion resistance of the tetrafunctional epoxy resin to the metal surface, and better resists the adverse effects of the external environment. Stir evenly, heat to 100°C, and then add the remaining amount of The tetrafunctional epoxy resin EMTE350 was reacted for 1 hour. After the reaction, the temperature was lowered to 85°C. The mixture was transferred to a high-speed disperser, and 100 mL of deionized water was added. The mixture was sheared and dispersed for 0.5 hour. The speed was controlled at 1600 rpm and the mixture was discharged at room temperature. The tetrafunctional epoxy resin was emulsified with polyetheramine as a hydrophilic chain extender and AGE as a regulator to form a stable epoxy emulsion. At the same time, the addition of the hydrophilic chain extender can reduce the surface tension of the epoxy emulsion, promote the penetration of the emulsion into smaller locations, and enhance the effectiveness and comprehensiveness of the anti-rust effect to obtain a water-based tetrafunctional epoxy emulsion.

[0052] (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 10 mL of water, stir evenly, then add citric acid, the amount of citric acid added is 0.4 g, citric acid can adjust the pH value of the sol, keep it in a stable acid-base environment, which is beneficial to improve the coating property, and dissolve it by ultrasound, the ultrasound temperature is 30°C, the ultrasound power is 600W, and the ultrasound time is 20 minutes. The silica sol has good film-forming property and stability, and can form a dense protective film on the metal surface, effectively isolating oxygen and moisture in the air, and preventing the oxidation process of the metal surface. The protective film formed by the silica sol has excellent weather resistance and corrosion resistance, can maintain the anti-rust effect for a long time in harsh environments, can withstand the influence of harsh environments such as high temperature and high humidity, and maintain stable and effective anti-rust ability, thereby obtaining silica sol;

[0053] (3) Add the silica sol described in step (2) to the water-based tetrafunctional epoxy emulsion described in step (1), stir for 5 minutes, and then ultrasonicate for 5 minutes. Use the silica sol as a film-forming matrix to perform composite modification on the water-based tetrafunctional epoxy emulsion. First, the surface tension of the epoxy emulsion is reduced, which further promotes the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure formed by the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, uniform and smooth, which helps to maintain a long-term stable and effective anti-rust effect. Then, the water resistance of the silica sol can improve the disadvantage of the epoxy emulsion that it is easy to absorb moisture, reduce the adverse effects of moisture on the curing efficiency of the epoxy emulsion and the adhesion effect after curing, and obtain the silica sol-modified epoxy emulsion.

[0054] The preparation method of the rust-proof filler specifically comprises the following steps:

[0055] a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear and take out, add 20.0g graphite powder and stir evenly, put it into a blast drying oven at 80℃ to react for 5h, pour the pre-oxidized product into 3 times the amount of deionized water, wash and filter it to neutrality several times, dry it at 60℃ for 10h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, place it in an ice water bath and stir it mechanically to make it uniform, then add 60.0g potassium permanganate, slowly heat to 35℃ to react for 1h, then add 920mL deionized water at a uniform rate, and control the temperature at 85℃ during this period , then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, then add 80mL concentrated hydrochloric acid, let stand, wash 3 times with 30% hydrochloric acid aqueous solution, put into dialysis bag for dialysis, remove impurity ions, ultrasonically disperse in anhydrous ethanol, filter, freeze-dry, the graphene oxide obtained by chemical oxidation contains a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups, which not only improves its solubility in polar solvents, but also makes the graphene oxide easy to modify, which can further enhance its anti-corrosion performance. Moreover, the lamellar structure of graphene oxide can effectively inhibit the infiltration, penetration and diffusion of corrosive media to obtain graphene oxide;

[0056] b. Weigh 0.1 g of the graphene oxide described in step a and add it to 150 mL of deionized water, ultrasonicate for 2 h to make it evenly dispersed, then add 1 mL of a phytic acid aqueous solution with a mass fraction of 60%, continue ultrasonication for 20 min, then stir and reflux in an oil bath at 80 ° C for 8 h, filter and wash until neutral, and freeze-dry. The addition of phytic acid makes the sheet structure of graphene oxide more irregular, and the sheets are cross-linked and stacked with each other, which increases the specific surface area and the amount of wrinkles, thereby enhancing the shielding performance, which is conducive to achieving a better anti-rust effect. In addition, phytic acid can also form complexes with metal ions such as iron, reduce the activity of metal ions, inhibit their generation and oxidation, thereby extending the durability of the anti-rust coating, improving its anti-rust performance, and obtaining phytic acidized graphene oxide;

[0057] c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions. The amount of phytated graphene oxide added is 50 mg. The structural characteristics of phytated graphene oxide increase the loading capacity and loading stability of zinc ions. Weigh 0.4 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water. Dissolve 0.6 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion and stir for 4 h to ensure sufficient adsorption of zinc ions. Then, drop the ammonium molybdate solution into the mixed solution, and add ammonia water to adjust. The pH value is lowered to 8.0, and then filtered, washed and dried to prepare a composite material of zinc molybdate and phytic acid graphene oxide. Since both zinc molybdate and phytic acid graphene oxide have flaky structures, the composite material formed by the two is similar to a sandwich structure, which prolongs the penetration path of the external corrosive medium. At the same time, the composite material has a large surface area, and there is a certain distance between the zinc molybdate particles, which is conducive to the synergistic effect of the two. The introduction of phytic acid graphene oxide improves the dispersibility of the zinc molybdate particles, and zinc molybdate also reduces the aggregation of phytic acid graphene oxide, which significantly improves the protective effect of the anti-rust coating to obtain an anti-rust filler.

[0058] This embodiment provides a method for preparing a high-efficiency and long-acting rust inhibitor, which specifically comprises the following steps:

[0059] The anti-rust filler was dispersed in 10 mL of deionized water, and then added to the silica sol-modified epoxy emulsion at a speed of 500 rpm, followed by the addition of TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide. The antibacterial and antifungal effect of nano zinc oxide also has a positive effect on the anti-rust performance of the coating. The mixture was stirred for 4 hours, and then EH2168 epoxy curing agent was added. The stirring was continued for 5 minutes. The prepared anti-rust coating can be sprayed on the metal surface to form a protective layer to effectively resist oxidation and corrosion. The anti-rust filler constructed a layer of anti-penetration structure in the silica sol-modified epoxy emulsion, which increased the density and spreadability of the coating, extended the invasion path of the corrosive medium, and expanded the extension range of the coating. At the same time, it also reduced the entry of water molecules, improved the heat resistance and stability of the coating, and enabled it to maintain a good anti-rust effect even in harsh environments. Thus, it is endowed with long-lasting and efficient anti-rust performance, and a high-efficiency and long-lasting rust inhibitor is obtained.

[0060] Example 3

[0061] This embodiment proposes a high-efficiency and long-lasting rust inhibitor, comprising the following components in parts by weight: 55 parts of silica sol combined with modified epoxy emulsion, 10 parts of rust-proof filler, 4 parts of TEGO-755W dispersant, 4 parts of TEGO-812 defoamer, 6.5 parts of nano zinc oxide, 17.5 parts of EH2168 epoxy curing agent, and 15 parts of deionized water.

[0062] The silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 40 parts of water-based four-functional epoxy emulsion and 25 parts of silica sol.

[0063] The rust-proof filler comprises the following components in parts by weight: 5.25 parts of phytated graphene oxide, 45 parts of ammonium molybdate tetrahydrate, and 65 parts of zinc acetate dihydrate.

[0064] The preparation method of silica sol combined with modified epoxy emulsion specifically comprises the following steps:

[0065] (1) Add polyetheramine M-3085, AGE and 1 / 2 of tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer. The molar amount of polyetheramine M-3085, AGE and tetrafunctional epoxy resin EMTE350 is 0.1 mol, which is beneficial to the grafting reaction between the reactants and the tetrafunctional epoxy resin, improves the dispersibility of the epoxy emulsion, and is also beneficial to the adhesion and corrosion resistance of the tetrafunctional epoxy resin to the metal surface, and better resists the adverse effects of the external environment. Stir evenly, heat to 105°C, and then add the remaining amount of tetrafunctional epoxy resin. The functional epoxy resin EMTE350 was reacted for 1.5 hours. After the reaction, the temperature was lowered to 85°C. The mixture was transferred to a high-speed disperser, and 125 mL of deionized water was added. The mixture was sheared and dispersed for 0.75 hours. The speed was controlled at 1700 rpm and the mixture was discharged at room temperature. The tetrafunctional epoxy resin was emulsified with polyetheramine as a hydrophilic chain extender and AGE as a regulator to form a stable epoxy emulsion. At the same time, the addition of the hydrophilic chain extender can reduce the surface tension of the epoxy emulsion, promote the penetration of the emulsion into smaller locations, enhance the effectiveness and comprehensiveness of the anti-rust effect, and obtain a water-based tetrafunctional epoxy emulsion.

[0066] (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 15 mL of water, stir evenly, then add citric acid, the amount of citric acid added is 0.5 g, citric acid can adjust the pH value of the sol, keep it in a stable acid-base environment, which is beneficial to improve the coating property, and dissolve it by ultrasound, the ultrasound temperature is 35°C, the ultrasound power is 700W, and the ultrasound time is 25 minutes. The silica sol has good film-forming property and stability, and can form a dense protective film on the metal surface, effectively isolating oxygen and moisture in the air, and preventing the oxidation process of the metal surface. The protective film formed by the silica sol has excellent weather resistance and corrosion resistance, can maintain the anti-rust effect for a long time in harsh environments, can withstand the influence of harsh environments such as high temperature and high humidity, and maintain stable and effective anti-rust ability, thereby obtaining silica sol;

[0067] (3) Add the silica sol described in step (2) to the water-based tetrafunctional epoxy emulsion described in step (1), stir for 10 minutes, and then ultrasonicate for 10 minutes. Use the silica sol as a film-forming matrix to perform composite modification on the water-based tetrafunctional epoxy emulsion. First, the surface tension of the epoxy emulsion is reduced, which further promotes the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure formed by the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, uniform and smooth, which helps to maintain a long-term stable and effective anti-rust effect. Then, the water resistance of the silica sol can improve the disadvantage of the epoxy emulsion that it is easy to absorb moisture, reduce the adverse effects of moisture on the curing efficiency of the epoxy emulsion and the adhesion effect after curing, and obtain the silica sol-modified epoxy emulsion.

[0068] The preparation method of the rust-proof filler specifically comprises the following steps:

[0069] a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear and take out, add 20.0g graphite powder and stir evenly, put it into a blast drying oven at 80℃ to react for 5.5h, pour the pre-oxidized product into 4 times the amount of deionized water, wash and filter it to neutrality several times, dry it at 60℃ for 11h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, place it in an ice water bath and stir it mechanically to make it uniform, then add 60.0g potassium permanganate, slowly heat to 35℃ and react for 1.5h, then add 920mL deionized water at a uniform rate, and control the temperature at 85℃ during the reaction. ℃, then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, then add 80mL concentrated hydrochloric acid, let it stand, wash it 4 times with a 32.5% hydrochloric acid aqueous solution, put it into a dialysis bag for dialysis, remove the impurity ions, ultrasonically disperse it in anhydrous ethanol, filter it, and freeze-dry it. The graphene oxide obtained by chemical oxidation contains a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups, which not only improves its solubility in polar solvents, but also makes it easy to modify the graphene oxide, which can further enhance its anti-corrosion performance. Moreover, the lamellar structure of graphene oxide can effectively inhibit the infiltration, penetration and diffusion of corrosive media to obtain graphene oxide;

[0070] b. Weigh 0.15 g of the graphene oxide described in step a and add it to 150 mL of deionized water, ultrasonicate for 2.5 h to make it evenly dispersed, then add 2 mL of a phytic acid aqueous solution with a mass fraction of 65%, continue ultrasonication for 25 min, then stir and reflux in an oil bath at 90 ° C for 10 h, filter and wash until neutral, and freeze-dry. The addition of phytic acid makes the sheet structure of graphene oxide more irregular, and the sheets are cross-linked and stacked with each other, which increases the specific surface area and the amount of wrinkles, thereby enhancing the shielding performance, which is conducive to achieving a better anti-rust effect. In addition, phytic acid can also form complexes with metal ions such as iron, reduce the activity of metal ions, inhibit their generation and oxidation, thereby extending the durability of the anti-rust coating, improving its anti-rust performance, and obtaining phytic acidized graphene oxide;

[0071] c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions. The amount of phytated graphene oxide added is 75 mg. The structural characteristics of phytated graphene oxide increase the loading capacity and loading stability of zinc ions. Weigh 0.45 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water. Dissolve 0.65 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion and stir for 4.5 h to ensure sufficient adsorption of zinc ions. Then, drop the ammonium molybdate solution into the mixed solution and add ammonia water. The pH value was adjusted to 8.0, and then filtered, washed and dried to prepare a composite material of zinc molybdate and phytated graphene oxide. Since both zinc molybdate and phytated graphene oxide have flaky structures, the composite material formed by the two is similar to a sandwich structure, which prolongs the penetration path of the external corrosive medium. At the same time, the composite material has a large surface area, and there is a certain distance between the zinc molybdate particles, which is conducive to the synergistic effect of the two. The introduction of phytated graphene oxide improves the dispersibility of the zinc molybdate particles, and zinc molybdate also reduces the aggregation of phytated graphene oxide, which significantly improves the protective effect of the anti-rust coating to obtain an anti-rust filler.

[0072] This embodiment provides a method for preparing a high-efficiency and long-acting rust inhibitor, which specifically comprises the following steps:

[0073] The anti-rust filler was dispersed in 15 mL of deionized water, and then added to the silica sol-modified epoxy emulsion at a speed of 550 rpm, followed by the addition of TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide. The antibacterial and antifungal effect of nano zinc oxide also has a positive effect on the anti-rust performance of the coating. The mixture was stirred for 4.5 hours, and then EH2168 epoxy curing agent was added. The stirring was continued for 7.5 minutes. The prepared anti-rust coating can be sprayed on the metal surface to form a protective layer to effectively resist oxidation and corrosion. The anti-rust filler constructed a layer of anti-penetration structure in the silica sol-modified epoxy emulsion, which increased the density and spreadability of the coating, extended the invasion path of the corrosive medium, and expanded the extension range of the coating. At the same time, it also reduced the entry of water molecules, improved the heat resistance and stability of the coating, and enabled it to maintain a good anti-rust effect even in harsh environments. Thus, it is endowed with long-lasting and efficient anti-rust performance, and a high-efficiency and long-lasting rust inhibitor is obtained.

[0074] Example 4

[0075] This embodiment proposes a high-efficiency and long-lasting rust inhibitor, comprising the following components in parts by weight: 60 parts of silica sol combined with modified epoxy emulsion, 8 parts of rust-proof filler, 5 parts of TEGO-755W dispersant, 5 parts of TEGO-812 defoamer, 5 parts of nano zinc oxide, 20 parts of EH2168 epoxy curing agent, and 20 parts of deionized water.

[0076] The silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 30 parts of water-based four-functional epoxy emulsion and 30 parts of silica sol.

[0077] The rust-proof filler comprises the following components in parts by weight: 0.5 parts of phytated graphene oxide, 50 parts of ammonium molybdate tetrahydrate, and 60 parts of zinc acetate dihydrate.

[0078] The preparation method of silica sol combined with modified epoxy emulsion specifically comprises the following steps:

[0079] (1) Add polyetheramine M-3085, AGE and 1 / 2 of the tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer. The molar amount of polyetheramine M-3085, AGE and the tetrafunctional epoxy resin EMTE350 is 0.1 mol, which is beneficial to the grafting reaction between the reactants and the tetrafunctional epoxy resin, improves the dispersibility of the epoxy emulsion, and is also beneficial to the adhesion and corrosion resistance of the tetrafunctional epoxy resin to the metal surface, and better resists the adverse effects of the external environment. Stir evenly, heat to 110°C, and then add the remaining amount of The tetrafunctional epoxy resin EMTE350 was reacted for 1 hour. After the reaction, the temperature was lowered to 85°C. The mixture was transferred to a high-speed disperser, and 150 mL of deionized water was added. The mixture was sheared and dispersed for 0.5 hour. The speed was controlled at 1800 rpm and the mixture was discharged at room temperature. The tetrafunctional epoxy resin was emulsified with polyetheramine as a hydrophilic chain extender and AGE as a regulator to form a stable epoxy emulsion. At the same time, the addition of the hydrophilic chain extender can reduce the surface tension of the epoxy emulsion, promote the penetration of the emulsion into smaller locations, and enhance the effectiveness and comprehensiveness of the anti-rust effect to obtain a water-based tetrafunctional epoxy emulsion.

[0080] (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 20 mL of water, stir evenly, then add citric acid, the amount of citric acid added is 0.4 g, citric acid can adjust the pH value of the sol, keep it in a stable acid-base environment, which is beneficial to improve the coating property, and dissolve it by ultrasound, the ultrasound temperature is 40°C, the ultrasound power is 800W, and the ultrasound time is 20 minutes. The silica sol has good film-forming property and stability, and can form a dense protective film on the metal surface, effectively isolating oxygen and moisture in the air, and preventing the oxidation process of the metal surface. The protective film formed by the silica sol has excellent weather resistance and corrosion resistance, can maintain the anti-rust effect for a long time in harsh environments, can withstand the influence of harsh environments such as high temperature and high humidity, and maintain stable and effective anti-rust ability, thereby obtaining silica sol;

[0081] (3) Add the silica sol described in step (2) to the water-based tetrafunctional epoxy emulsion described in step (1), stir for 5 minutes, and then ultrasonicate for 5 minutes. Use the silica sol as a film-forming matrix to perform composite modification on the water-based tetrafunctional epoxy emulsion. First, the surface tension of the epoxy emulsion is reduced, which further promotes the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure formed by the silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more firm, uniform and smooth, which helps to maintain a long-term stable and effective anti-rust effect. Then, the water resistance of the silica sol can improve the disadvantage of the epoxy emulsion that it is easy to absorb moisture, reduce the adverse effects of moisture on the curing efficiency of the epoxy emulsion and the adhesion effect after curing, and obtain the silica sol-modified epoxy emulsion.

[0082] The preparation method of the rust-proof filler specifically comprises the following steps:

[0083] a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear and take out, add 20.0g graphite powder and stir evenly, put it into a blast drying oven at 80℃ to react for 5h, pour the pre-oxidized product into 5 times the amount of deionized water, wash and filter it to neutrality several times, dry it at 60℃ for 10h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, place it in an ice water bath and stir it mechanically to make it uniform, then add 60.0g potassium permanganate, slowly heat to 35℃ to react for 1h, then add 920mL deionized water at a uniform rate, and control the temperature at 85℃ during this period , then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, then add 80mL concentrated hydrochloric acid, let stand, wash 5 times with 35% hydrochloric acid aqueous solution, put into dialysis bag for dialysis, remove impurity ions, ultrasonically disperse in anhydrous ethanol, filter, freeze-dry, the graphene oxide obtained by chemical oxidation contains a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups, which not only improves its solubility in polar solvents, but also makes the graphene oxide easy to modify, which can further enhance its anti-corrosion performance. Moreover, the lamellar structure of graphene oxide can effectively inhibit the infiltration, penetration and diffusion of corrosive media to obtain graphene oxide;

[0084] b. Weigh 0.2 g of the graphene oxide described in step a and add it to 150 mL of deionized water, ultrasonicate for 2 h to make it evenly dispersed, then add 1 mL of a phytic acid aqueous solution with a mass fraction of 70%, continue ultrasonication for 20 min, then stir and reflux in an oil bath at 100 ° C for 8 h, filter and wash until neutral, and freeze-dry. The addition of phytic acid makes the sheet structure of graphene oxide more irregular, and the sheets are cross-linked and stacked with each other, which increases the specific surface area and the amount of wrinkles, thereby enhancing the shielding performance, which is conducive to achieving a better anti-rust effect. In addition, phytic acid can also form complexes with metal ions such as iron, reduce the activity of metal ions, inhibit their generation and oxidation, thereby extending the durability of the anti-rust coating, improving its anti-rust performance, and obtaining phytic acidized graphene oxide;

[0085] c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions. The amount of phytated graphene oxide added is 50 mg. The structural characteristics of phytated graphene oxide increase the loading capacity and loading stability of zinc ions. Weigh 0.5 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water. Dissolve 0.6 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion and stir for 4 h to ensure sufficient adsorption of zinc ions. Then, drop the ammonium molybdate solution into the mixed solution, and add ammonia water to adjust. The pH value is lowered to 8.0, and then filtered, washed and dried to prepare a composite material of zinc molybdate and phytic acid graphene oxide. Since both zinc molybdate and phytic acid graphene oxide have flaky structures, the composite material formed by the two is similar to a sandwich structure, which prolongs the penetration path of the external corrosive medium. At the same time, the composite material has a large surface area, and there is a certain distance between the zinc molybdate particles, which is conducive to the synergistic effect of the two. The introduction of phytic acid graphene oxide improves the dispersibility of the zinc molybdate particles, and zinc molybdate also reduces the aggregation of phytic acid graphene oxide, which significantly improves the protective effect of the anti-rust coating to obtain an anti-rust filler.

[0086] This embodiment provides a method for preparing a high-efficiency and long-acting rust inhibitor, which specifically comprises the following steps:

[0087] The anti-rust filler was dispersed in 20 mL of deionized water, and then added to the silica sol-modified epoxy emulsion at a speed of 600 rpm, followed by the addition of TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide. The antibacterial and antifungal effect of nano zinc oxide also has a positive effect on the anti-rust performance of the coating. The mixture was stirred for 4 hours, and then EH2168 epoxy curing agent was added. The stirring was continued for 5 minutes. The prepared anti-rust coating can be sprayed on the metal surface to form a protective layer to effectively resist oxidation and corrosion. The anti-rust filler constructed a layer of anti-penetration structure in the silica sol-modified epoxy emulsion, which increased the density and spreadability of the coating, extended the invasion path of the corrosive medium, and expanded the extension range of the coating. At the same time, it also reduced the entry of water molecules, improved the heat resistance and stability of the coating, and enabled it to maintain a good anti-rust effect even in harsh environments. Thus, it is endowed with long-lasting and efficient anti-rust performance, and a high-efficiency and long-lasting rust inhibitor is obtained.

[0088] Comparative Example 1

[0089] This comparative example provides a high-efficiency and long-lasting rust inhibitor, which differs from Example 1 in that the silica sol-modified epoxy emulsion does not contain silica sol and polyetheramine M-3085; the preparation method of the silica sol-modified epoxy emulsion does not include step (2); the preparation method of the rust-proof filler is the same as that of Example 1; and the preparation method of the high-efficiency and long-lasting rust inhibitor is the same as that of Example 1.

[0090] Comparative Example 2

[0091] This comparative example provides a high-efficiency and long-lasting rust inhibitor, which differs from Example 1 in that the rust-proof filler does not contain graphene oxide; the preparation method of silica sol combined with modified epoxy emulsion is the same as that of Example 1; the preparation method of magnetic nanowire microsphere carrier does not include step a; the preparation method of the high-efficiency and long-lasting rust inhibitor is the same as that of Example 1.

[0092] Comparative Example 3

[0093] This comparative example provides a high-efficiency and long-lasting rust inhibitor, which differs from Example 1 in that the rust-proof filler does not contain phytic acid; the preparation method of silica sol combined with modified epoxy emulsion is the same as that of Example 1; the preparation method of magnetic nanowire microsphere carrier does not include step b; the preparation method of the high-efficiency and long-lasting rust inhibitor is the same as that of Example 1.

[0094] Experimental Example 1

[0095] Anti-rust effectiveness test

[0096] Test samples: high-efficiency and long-lasting rust inhibitors prepared in Examples 1-4 and Comparative Examples 1-3.

[0097] Test method: The test piece is made of Z30 first-grade cast iron with a specification of 50mm×25mm×(3-6)mm. The specific style is in accordance with the standard of GB / T35759-017. The grinding and cleaning of the test piece are processed according to the method 5.1.2 of GB / T35759-2017 for use. Then the test sample is sprayed on the surface of the test piece. After drying, according to the national standard GB / T1771-2007, a 3.5% NaCl solution (pH value is 6.5-7.2) is used for salt spray resistance test for 200h. The surface of the test piece is scanned and measured by an image scanner. The total surface area of ​​the test piece and the rust area after the salt spray resistance test are calculated by computer software. The rust rate (%) is calculated according to the following formula:

[0098] Corrosion rate (%) = Corrosion area (mm 2 ) / total area (mm 2 )×100%

[0099] Figure 3It is a result diagram of the corrosion rate of Examples 1-4 and Comparative Examples 1-3; as shown in the figure, the corrosion rate of Examples 1-4 is 0.5-2.5%, indicating that the anti-rust effectiveness is good; the corrosion rate of Comparative Examples 1-3 is 5.8-10.3%, indicating that the anti-rust effectiveness is general; the silica sol-modified epoxy emulsion of Comparative Example 1 does not contain silica sol and polyetheramine M-3085, and the epoxy emulsion cannot be modified, which is not conducive to reducing the surface tension of the epoxy emulsion, nor is it conducive to increasing the firmness of the anti-rust protective layer, resulting in general anti-rust effectiveness; the anti-rust filler of Comparative Example 2 does not contain graphene oxide, and the double layer cannot exert the inhibitory effect of the infiltration, penetration and diffusion of the corrosive medium, nor can it use its layer structure to load zinc ions, which increases the aggregation of zinc molybdate particles and limits the effectiveness, resulting in general anti-rust effectiveness; the anti-rust filler of Comparative Example 3 does not contain phytic acid, and the graphene oxide layers cannot be cross-linked and stacked with each other, which is not conducive to enhancing the shielding performance, and relatively shortens the penetration path of the external corrosive medium, resulting in general anti-rust effectiveness.

[0100] Experimental Example 2

[0101] Anti-rust long-term effect experiment

[0102] Test samples: high-efficiency and long-lasting rust inhibitors prepared in Examples 1-4 and Comparative Examples 1-3.

[0103] Test method: The test piece is made of Z30 first-grade cast iron with a specification of 50mm×25mm×(3-6)mm. The specific style is in accordance with the standard of GB / T35759-017. The grinding and cleaning of the test piece are processed according to the method 5.1.2 in GB / T35759-2017 for standby use. The test sample is then sprayed on the surface of the test piece. After drying, according to the national standard GB / T1771-2007, at a temperature of 37±5℃ and a humidity of 60±5%, a 3.5% NaCl solution (pH value of 6.5-7.2) is used for salt spray resistance test. The test time is 200h, 300h, 400h, 500h, and 600h respectively. The surface of the test piece is scanned and measured by an image scanner. The total area of ​​the test piece surface and the rust area after the salt spray resistance test are calculated by computer software, and the rust rate (%) at different times under high temperature and high humidity is obtained.

[0104] Figure 4The results of the corrosion rates of Examples 1-4 and Comparative Examples 1-3 at different times under high temperature and high humidity are shown in the figure; as shown in the figure, the corrosion rates of Examples 1-4 at 200h, 300h, 400h, 500h, and 600h are 0.6-2.7%, 0.7-2.8%, 0.9-3.1%, 1.2-3.5%, and 1.5-3.9%, respectively, indicating that the long-term anti-rust effect is better; the corrosion rates of Comparative Examples 1-3 at 200h, 300h, 400h, 500h, and 600h are 6.1-10.6%, 6.4-10.9%, 6.7-11.3%, 7.2-11.8%, and 7.7-12.4%, respectively, indicating that the long-term anti-rust effect is general; the silica sol-modified epoxy emulsion of Comparative Example 1 does not contain silica sol and polyetheramine M-3085, It is unable to improve the resistance of epoxy emulsion to the influence of adverse environments such as high temperature and high humidity, which is not conducive to the stability of the anti-rust protective layer, resulting in general long-term anti-rust effect; the anti-rust filler of comparative example 2 does not contain graphene oxide, and cannot form a composite material with zinc molybdate, which increases the aggregation and agglomeration of zinc molybdate, is not conducive to improving the water resistance and heat resistance of the system, thereby having a negative impact on the stability of the anti-rust coating, resulting in general long-term anti-rust effect; the anti-rust filler of comparative example 3 does not contain phytic acid, and cannot increase the complexity of the graphene oxide sheet structure, which is not conducive to the density and isolation of the anti-rust coating, thereby increasing the entry of moisture, and is not conducive to increasing the loading amount and loading stability of zinc molybdate, limiting the improvement of the water resistance and heat resistance of the anti-rust coating, and at the same time cannot exert its own corrosion inhibition performance, resulting in general long-term anti-rust effect.

[0105] The above experimental results show that the anti-rust effectiveness and long-term anti-rust performance of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using silica sol combined with modified epoxy emulsion and anti-rust filler has better anti-rust effectiveness and better long-term anti-rust performance. The water-based tetrafunctional epoxy emulsion is modified with silica sol as the film-forming matrix, which reduces the surface tension of the epoxy emulsion and is beneficial to the penetration and extension of the epoxy emulsion. Secondly, the uniform microscopic pore structure of silica sol enhances the hardness and wear resistance of the epoxy emulsion, making the anti-rust protective layer more solid. , which is conducive to ensuring long-term stable and effective anti-rust ability. Moreover, the addition of silica sol can also act as an anti-precipitation agent to reduce the precipitation of solid substances such as other fillers, so as to fully maximize the performance of each component; the anti-rust filler is a composite material of zinc molybdate and phytated graphene oxide, which has a large surface area and a sandwich-like structure, which prolongs the penetration path of external corrosive media, helps to reduce the surface tension of epoxy emulsion, and further enhances the stability of the rust inhibitor in high temperature and high humidity environment, thereby helping to exert long-term and efficient anti-rust performance.

[0106] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0107] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-efficiency and long-lasting rust inhibitor, characterized in that: The high-efficiency and long-lasting rust inhibitor comprises the following components in parts by weight: 50-60 parts of silica sol combined with modified epoxy emulsion, 8-12 parts of rust-proof filler, 3-5 parts of TEGO-755W dispersant, 3-5 parts of TEGO-812 defoamer, 5-8 parts of nano zinc oxide, 15-20 parts of EH2168 epoxy curing agent, and 10-20 parts of deionized water; the silica sol combined with modified epoxy emulsion comprises the following components in parts by weight: 30-50 parts of water-based tetrafunctional epoxy emulsion and 20-30 parts of silica sol; the rust-proof filler comprises the following components in parts by weight: 0.5-10 parts of phytated graphene oxide, 40-50 parts of ammonium molybdate tetrahydrate, and 60-70 parts of zinc acetate dihydrate.

2. A method for preparing the high-efficiency and long-lasting rust inhibitor according to claim 1, characterized in that: The specific steps include: Disperse the anti-rust filler in 10-20 mL of deionized water, add it to the silica sol-modified epoxy emulsion at a speed of 500-600 rpm, then add TEGO-755W dispersant, TEGO-812 defoamer and nano zinc oxide, stir for 4-5 hours, then add EH2168 epoxy curing agent, continue stirring for 5-10 minutes to obtain a high-efficiency and long-lasting rust inhibitor.

3. The method for preparing the high-efficiency and long-acting rust inhibitor according to claim 2, characterized in that: The preparation method of the silica sol combined with modified epoxy emulsion specifically comprises the following steps: (1) Add polyetheramine M-3085, AGE and 1 / 2 of tetrafunctional epoxy resin EMTE350 into a four-necked flask equipped with a stirrer, a condenser and a thermometer, stir evenly, heat to 100-110°C, then add the remaining amount of tetrafunctional epoxy resin EMTE350, continue to react for 1-2 hours, cool to 85°C after the reaction, transfer the mixture to a high-speed disperser, add 100-150 mL of deionized water, perform shear dispersion for 0.5-1 hour, control the speed to 1600-1800 rpm, reduce to room temperature and discharge to obtain a water-based tetrafunctional epoxy emulsion; (2) Add 26 mL of vinyl triethoxysilane liquid and 6 mL of dimethyl dimethoxysilane liquid to a mixed solution of 200 mL of anhydrous ethanol and 10-20 mL of water, stir evenly, then add citric acid, and dissolve it by ultrasonication at a temperature of 30-40°C, an ultrasonic power of 600-800 W, and an ultrasonic time of 20-30 min to obtain a silica sol; (3) Add the silica sol described in step (2) to the aqueous tetrafunctional epoxy emulsion described in step (1), stir for 5-15 minutes, and then ultrasonicate for 5-15 minutes to obtain a silica sol-modified epoxy emulsion.

4. The method for preparing the high-efficiency and long-acting rust inhibitor according to claim 3, characterized in that: In step (1), the molar amounts of polyetheramine M-3085, AGE and tetrafunctional epoxy resin EMTE350 are all 0.1 mol.

5. The method for preparing the high-efficiency and long-acting rust inhibitor according to claim 4, characterized in that: In step (2), the amount of citric acid added is 0.4-0.6 g.

6. The method for preparing the high-efficiency and long-acting rust inhibitor according to claim 5, characterized in that: The preparation method of the rust-proof filler specifically comprises the following steps: a. Put 10.0g potassium persulfate powder, 10.0g phosphorus pentoxide powder and 30mL concentrated sulfuric acid into a water bath at 80℃, stir until clear, take out, add 20.0g graphite powder and stir evenly, put into a blast drying oven at 80℃ to react for 5-6h, pour the pre-oxidized product into 3-5 times the amount of deionized water, wash and filter it to neutrality for many times, dry it at 60℃ for 10-12h, then add 20.0g pre-oxidized graphite powder and 460mL concentrated sulfuric acid into a three-necked flask, put it in an ice water bath and stir it mechanically. uniformly, then add 60.0g potassium permanganate, slowly heat to 35℃, react for 1-2h, then add 920mL deionized water at a uniform rate, control the temperature at 85℃, then add 2.8L deionized water and 50mL hydrogen peroxide liquid, stir for 30min, add 80mL concentrated hydrochloric acid, let stand, wash 3-5 times with 30-35% hydrochloric acid aqueous solution, put into dialysis bag for dialysis, remove impurity ions, ultrasonically disperse in anhydrous ethanol, filter, and freeze-dry to obtain graphene oxide; b. Weigh 0.1-0.2 g of the graphene oxide described in step a, add it into 150 mL of deionized water, and ultrasonicate it for 2-3 h to make it evenly dispersed, then add 1-3 mL of a phytic acid aqueous solution with a mass fraction of 60-70%, continue ultrasonication for 20-30 min, and then stir and reflux in an oil bath at 80-100 ° C for 8-12 h, filter and wash until neutral, and freeze-dry to obtain phytic acid-treated graphene oxide; c. Disperse the phytated graphene oxide described in step b in 50 mL of deionized water under ultrasonic conditions, weigh 0.4-0.5 g of ammonium molybdate tetrahydrate and dissolve it in 25 mL of deionized water, and dissolve 0.6-0.7 g of zinc acetate dihydrate in 25 mL of deionized water. Under stirring, slowly add the zinc acetate solution to the phytated graphene oxide dispersion, stir for 4-5 hours to ensure sufficient adsorption of zinc ions, then add the ammonium molybdate solution dropwise to the mixed solution, add ammonia water to adjust the pH to 8.0, and then filter, wash, and dry to obtain an antirust filler.

7. The method for preparing the high-efficiency and long-acting rust inhibitor according to claim 6, characterized in that: In step c, the amount of phytated graphene oxide added is 50-100 mg.